2008
DOI: 10.1111/j.1439-0426.2007.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass-marking of brown trout (Salmo trutta L.) larvae by alizarin: method and evaluation of stocking

Abstract: SummaryThis study describes otolith marking of brown trout (Salmo trutta L.) larvae by immersion in different solutions of alizarin red S (ARS). The best results were obtained after marking with ARS at a concentration of 150 mg L )1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 35 publications
8
52
0
Order By: Relevance
“…Despite variations in the quality and lasting of the marks, fluorescent signals were detected in both treatments and all the structures analyzed. These findings are in agreement with several studies that showed ARS effectiveness for immersion marking, as well as its potential in biological research and evaluation of stock enhancement programs (Bashey, 2004;Baer & Rösch, 2008;Crook et al, 2007;Liu et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite variations in the quality and lasting of the marks, fluorescent signals were detected in both treatments and all the structures analyzed. These findings are in agreement with several studies that showed ARS effectiveness for immersion marking, as well as its potential in biological research and evaluation of stock enhancement programs (Bashey, 2004;Baer & Rösch, 2008;Crook et al, 2007;Liu et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…The most commonly used were oxytetracycline (OTC), hydrochloride, calcein, alizarin complexone (AC) and alizarin red S (ARS). However, calcein, ARS and AC performed better than other chemicals because: marks can be detected and read clearly, the effect over survival rates was proven to be less negative, and all can be used in salt water (Tsukamoto et al, 1989;Van der Walt & Faragher, 2003;Taylor et al, 2005;Baer & Rösch, 2008;Liu et al, 2009). Even though previously performed experiments using calcein have obtained clear and long-lasting marks, this chemical compound is expensive and was found to be toxic when fishes were exposed to it for long periods of time (Brooks et al, 1994;Bumguardner & King, 1996;Frenkel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The present study approves the method of mu ltip le marking of sea trout larvae with a 3h immersion in a 200 mg A RS L -1 solution without requiring prior osmotic induction. This corresponds with the results presented in previous studies where 100% effect ive ARS concentrations for batch marking of Salmo trutta L. larvae ranged between 100-150 mg ARS L -1 , which also kept fish mo rtality below 5% (Baer & Rösch, 2008;Caudron & Champigneulle, 2006, 2009Niva et al, 2005;Unfer & Pinter, 2013). At higher alizarin concentrations, up to 300 mg ARS L -1 , high fish mortality (about 95%) was observed immed iately after a 3h immersion (Baer & Rösch, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…This corresponds with the results presented in previous studies where 100% effect ive ARS concentrations for batch marking of Salmo trutta L. larvae ranged between 100-150 mg ARS L -1 , which also kept fish mo rtality below 5% (Baer & Rösch, 2008;Caudron & Champigneulle, 2006, 2009Niva et al, 2005;Unfer & Pinter, 2013). At higher alizarin concentrations, up to 300 mg ARS L -1 , high fish mortality (about 95%) was observed immed iately after a 3h immersion (Baer & Rösch, 2008). Different results were reported by Unfer & Pinter (2013), who recorded a post-marking mortality rate of brown trout larvae of 0.8 Ind./day during 38 days, after immersion in 300 mg A RS L -1 for 3h.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation